Access to Knowledge in Egypt New Research on Intellectual Property, Innovation and Development - Shaver, Lea; Rizk, Nagla (Access to Knowledge, 2010)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. "This book is an important contribution to recovering a nuanced, contextually aware view of access to knowledge and global knowledge governance" Yochaie Benkler, Harvard Law School "This is a 'must read' for scholars and practioners interested in economic devlopment, cultural production and access to knowledge" Susan Sell, George Washington University This volume features five chapters on current issues facing intellectual property, innovation and development policy from the Egyptian perspective. These include: information and communications technology for development, copyright and comparative business models in music, open source software, patent reform and access to medicines, and the role of the Egyptian government in promoting access to knowledge internationally and domestically. Together these chapters offer an overview of the challenges and opportunities facing efforts to promote access to knowledge. Combining both theoretical and empirical approaches, the work will be of interest to scholars and practitioners dealing with intellectual property and innovation property the world over.